Job and Organizational Factors Determining Nurses' Work Stress at Regional General Hospital - Hardi S., Ikhram; Hapsah, Hapsah; Yuliati, Yuliati; Ramadhani, Syafhira (Universitas Airlangga, 2025)
Introduction: One of the government hospitals in South Sulawesi is facing various challenges related to nurses' working conditions, such as work stress. Preliminary data show that high work pressure, the nursing shift system, and the ratio of nurses to patients contribute to this condition and are predicted as risk factors that can affect the quality of work life for nurses. Methods: This study aim is to examine how organizational and job-related factors affect hospital nurses' work stress at regional hospital. Using a cross-sectional methodology, this study included 167 nurses out of 287 who were chosen by accident sampling. Questionnaires, observations, and interviews were used to gather data, which were then subjected to linear regression analysis (95% CI; α=0.05). Results: The results of this study indicate that work stress is significantly influenced by the job factor (p=0.000; β=0.415) and organizational factor (p=0.011; β= -0.229). Emotional demands are the most influential component of job factors on the emergence of stress. Conclusion: High job demands, especially emotional burden, significantly increase nurses' work stress, whereas good organizational support can reduce it. These findings indicate the importance of reducing emotional burden and increasing institutional support through mental resilience training, structured debriefing sessions, peer support systems, and psychological counseling services. The results of this study can also be used as a basis for policy making by hospital leaders to be more supportive of nurses' mental well-being and the sustainability of health service quality.